Creatinine-Based Formulae Poorly Match in the Classification of Hypofiltration or Hyperfiltration in a General Population of Adolescents: A Retrospective Analysis of a Cross-Sectional Study - Šebeková, Katarína; Gurecká, Radana; Tóthová, Ĺubomíra; Podracká, Ĺudmila (Frontiers in Pediatrics, 2021)
Pediatric formulae to estimate glomerular filtration rate (eGFR) give a broad range of values. Their consistency in assigning the subjects as hypofiltrating or hyperfiltrating is unknown. In 1993 apparently healthy adolescents (53.4% females) aged 14–17 years, we investigated the concordance of six creatinine-based formulae in the classification of the subjects into ≤ 5th or ≥95th percentile of eGFR, and the between-groups difference in the prevalence of cardiometabolic risk factors. Mean eGFR varied between 77 and 121 mL/min/1.73 m2. Arbitrary setting of hypofiltration or hyperfiltration to 5% returned 46 males and 53 females. At least one formula classified 89 males and 99 females as hypofiltrating and 105 males and 114 females as hyperfiltrating. All six formulae concordantly classified 15 males and 17 females as hypofiltrating and 9 and 14, respectively, as hyperfiltrating. Pairwise, formulae consistently classified hypofiltration in 42–87% of subjects with hyperfiltration in 28–94%. According to two out of the six formulae, hyperfiltration was associated with an increased prevalence of obesity and obesity-associated comorbidities. Hypofiltrating subjects did not manifest chronic kidney disease–associated comorbidities. Further studies in different populations of healthy adolescents are needed before it is possible to conclude which creatinine-based formula is appropriate for the classification of hypofiltration and hyperfiltration in nonclinical cohorts.